Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1478-3231.2011.02591.x
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricle enlargement and increased systolic velocity in the mitral valve are indirect markers of the hepatopulmonary syndrome

Abstract: We confirmed that in patients with cirrhosis, the development of HPS is associated with higher cardiac output and hyperdynamic circulation. Left ventricle enlargement and higher systolic velocity in the mitral valve represent satisfactory indirect markers of HPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…It is an interesting observation that patients with HPS were significantly younger than patients without HPS. This is also described by Pouriki et al (19). In other studies HPS patients were younger than patients without the disorder, although the age difference was not statistically significant (18,20).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It is an interesting observation that patients with HPS were significantly younger than patients without HPS. This is also described by Pouriki et al (19). In other studies HPS patients were younger than patients without the disorder, although the age difference was not statistically significant (18,20).…”
Section: Discussionsupporting
confidence: 80%
“…This is also described by Pouriki et al . . In other studies HPS patients were younger than patients without the disorder, although the age difference was not statistically significant .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Furthermore, patients with chronic liver disease and diagnosed HPS showed a significantly greater left atrial volume compared to the control group (55.1 ± 7.5 ml and 37.1 ± 9.3 ml, A-aО 2 : alveolar-arterial oxygen gradient; РаО 2 : partial pressure of oxygen respectively, p < 0.05); the sensitivity was 86.3% and specificity -81.2% [35]. These results indicate that left atrial enlargement could be used as diagnostic criteria for HPS [35,36]. The disadvantage of two-dimensional transthoracic contrast echocardiography is the inability to determine the type of vascular anomaly that caused a pulmonary shunt [37].…”
Section: Diagnostic Criteria For Hpsmentioning
confidence: 71%
“…Remarkably, left atrial volume equal or greater than 50 mL was suggested as a strong echocardiographic predictor of HPS in patients with liver cirrhosis (area under the receiver operating characteristic curve: 0.903, sensitivity 86.3%, specificity 81.2%)[ 126 ]. Left ventricular enlargement was also proposed as an independent, indirect echocardiographic marker of HPS[ 127 ]. In addition, higher systolic myocardial velocity of the mitral valve measured by tissue Doppler imaging technique was independently associated with HPS (odds ratio: 1.428, 95%CI: 1.049-1.943, P = 0.026), a finding implying left ventricular systolic dysfunction[ 127 ].…”
Section: Hps and Myocardial Functionmentioning
confidence: 99%